2021
DOI: 10.1186/s13722-021-00225-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating a brief alcohol intervention with tobacco addiction treatment in primary care: qualitative study of health care practitioner perceptions

Abstract: Background Randomized trials of complex interventions are increasingly including qualitative components to further understand factors that contribute to their success. In this paper, we explore the experiences of health care practitioners in a province wide smoking cessation program (the Smoking Treatment for Ontario Patients program) who participated in the COMBAT trial. This trial examined if the addition of an electronic prompt embedded in a Clinical Decision Support System (CDSS)—designed t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Passive prompts provide clinical guidance to the GP end-user without requiring any action on their part, while active prompts are automated clinical actions or alerts, which the user must either accept or override to proceed with their work ow (10). CDSS applications include those for the detection and management of cancer, sepsis, acute pain, hypertension, asthma, diabetes, alcohol and tobacco use, antibiotic prescribing, vaccination, medication adverse events, and pregnancy care (4,5,10,11,12,13,14,15,16,17,18,19,20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive prompts provide clinical guidance to the GP end-user without requiring any action on their part, while active prompts are automated clinical actions or alerts, which the user must either accept or override to proceed with their work ow (10). CDSS applications include those for the detection and management of cancer, sepsis, acute pain, hypertension, asthma, diabetes, alcohol and tobacco use, antibiotic prescribing, vaccination, medication adverse events, and pregnancy care (4,5,10,11,12,13,14,15,16,17,18,19,20).…”
Section: Resultsmentioning
confidence: 99%
“…Other identi ed barriers include costs in time and nances associated with the set up and maintenance of CDSS (3,5,28,30,31), lack of information technology (IT) support (10,25,39), challenges around content delivery and maintenance, concerns relating to information quality, risk of litigation, and the potential use of data by third parties (5,14,31,33,34,35,39). CDSS system mechanisms that also impact on end-user satisfaction include poor interface design, limited system exibility and functionality, hardware reliability and computing network issues, software malfunctions, limitations in end-user's IT literacy, and inadequate IT support and training (3,5,10,15,25,28,29,30,31,32,34,35,36,39,40,41).…”
Section: Utility Barriers and Facilitatorsmentioning
confidence: 99%
“…This result is comparable to findings from the wider health literature. For instance, Minian et al (2021) showed that the addition of an electronic prompt positively influenced the proportion of practitioners delivering a brief intervention relating to alcohol use, with 19/23 practitioners acknowledging the value of adding a validated screening tool to the baseline questionnaire. Participants did advise, however, that organisational and sociocultural factors need to be included as part of an electronic prompt design to increase its diagnostic value and reduce redundant alerts (Minian et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not come without its challenges. There is a concurrent need for clinician and societal education without which there is a risk of a lack of prompt engagement or prompt fatigue (Brenner et al ., 2017; Minian et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a pragmatic, hybrid type I effectiveness and implementation trial [ 39 ], which allowed for the simultaneous testing of intervention effectiveness and implementation feasibility in real-world settings. Health care practitioners in primary care settings often report barriers to offering comprehensive preventive health services, including not having enough time, skills, knowledge, or resources [ 40 ]. As a result, it is important to examine the effectiveness of the CDSS on patients’ behavior outcomes, as well as how the CDSS impacts health care practitioners’ ability to provide treatment to their patients.…”
Section: Methodsmentioning
confidence: 99%